2021
DOI: 10.2174/1386207323666201204135941
|View full text |Cite
|
Sign up to set email alerts
|

Neobavaisoflavone Demonstrates Valid Anti-tumor Effects in Non-Small- Cell Lung Cancer by Inhibiting STAT3

Abstract: Aim and Objective : Lung cancer is the most common cancer which contributes to the majority of death caused by cancer where non-small-cell lung cancer (NSCLC) accounts for approximately 85%. To treat NSCLC, STAT3 has been identified as a target with therapeutic potential. The neobavaisoflavone (NBIF) is one of the flavonoids of traditional Chinese medicine Psoralea corylifolial. Materials and Methods: Human NSCLC cell lines, PC-9, H460 and A549, were applied to determine NBIF’s antiproliferative effects thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The anti-cancer effects of NBIF have been demonstrated in several different tumor cell lines [ 34 , 37 , 38 , 39 , 40 ], including gliomas [ 34 , 38 ]. Previously, we have found that this isoflavone moderately decreased the viability of U-87 MG cells in a concentration-dependent manner, and slightly reduced the percentage of living cells at 100 μM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer effects of NBIF have been demonstrated in several different tumor cell lines [ 34 , 37 , 38 , 39 , 40 ], including gliomas [ 34 , 38 ]. Previously, we have found that this isoflavone moderately decreased the viability of U-87 MG cells in a concentration-dependent manner, and slightly reduced the percentage of living cells at 100 μM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen signaling pathway was related to many physiological processes of mammals, including reproduction, cardiovascular protection, and bone integrity [ 24 ]. The other pathways were related to anticancer and estrogen-like effects [ 11 , 25 , 26 ]. Besides the pharmacological mechanisms of anti-osteoporosis, anti-cancer, and estrogen-like effects, the pathways were also related to anti-inflammatory, antioxidant, neuroactive, and adrenergic effects [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neobavaisoflavone (NBIF) is a crucial component of Psoralea corylifolia L. that has been shown to have chemosensitizing benefits for treating glioma (85). It also can inhibit STAT3 activation and suppress NSCLC cell proliferation (86). Jufeng Guo et al (87) found that NBIF inhibited tumor growth in breast and small-cell lung cancer mice.…”
Section: Flavonoidsmentioning
confidence: 99%